Exploration of how 3D printing is influencing manufacturing businesses in Durban Kwazulu-Natal - Kostakis, Anastassios (The IIE, 2020)
According to Valtas and Sun (2016), 3D printing, also known as additive manufacturing technology, has been labelled the next big thing and could be as popular as cell phones in the future. The purpose of this study is to explore how 3D printing is influencing manufacturing businesses in Durban KwaZulu-Natal (KZN). According to Valtas and sun (2016), this could give insight into how 3D printing may be disruptive as well as create opportunities and contribute to a competitive advantage for businesses that are looking to adopt the technology in the future. This study aims to not only highlight the opportunities that arise with 3D printing, but also the negative influences it has on businesses. There has not been much research conducted on how 3D printing has influenced businesses which is why this research is relevant and the aim of the study is to contribute to closing the gap in the literature. To collect data for the current study, the researcher made use of semi-structured interviews as the data collection method since this method offered a more flexible approach to the interview process (Ryan, Coughlan & Cronin 2009). Two interviews were concluded and findings demonstrate that the potentially disruptive technology of 3D printing has already started to diffuse into businesses in Durban which brings many benefits such as cost reduction and a few challenges which include not being able to manufacture on a large scale.
Keywords: 3D printing; Manufacturing businesses; Business practices; Effects of 3D printing